Acute toxicity of dispersed crude oil on the cold-water copepod Calanus finmarchicus: Elusive implications of lipid content. Issue 13 (2nd August 2016) - Hansen, Bjørn Henrik; Jager, Tjalling; Altin, Dag; Øverjordet, Ida B.; Olsen, Anders J.; Salaberria, Iurgi; Nordtug, Trond
ABSTRACT: In this investigation, acute toxicity data were used from two previously reported studies where cold-water copepods were exposed to mechanically dispersed (MD) and chemically (CD) dispersed oil. In one of these studies, concentration-dependent mortality was observed, whereas no apparent relationship between exposure concentration and mortality was found in the other. The only marked difference between the studies is that copepods in the first experiment displayed a lower lipid sac volume (on average) than in the second one. In this study additional biometric data on lipid content were utilized and observed effects and toxicokinetics modeling applied in order to investigate whether differences in sensitivity between copepod cohorts might be explained by differences in lipid content. Results suggest that although a considerable lipid sac might retard toxicokinetics, the observed differences in lipid volume are not sufficient to explain differences in toxicity. Further, there are no apparent indications that acute toxic stress leads to lipid depletion, or that acute increased mortality rate selectively affects lipid-poor individuals. It is conceivable that other potential explanations exist, but the causal relationship between lipid content and increased mortality frequency remains elusive.